Computational fluid dynamics of the ascending aorta before the onset of type A aortic dissection. (12th September 2016) - Malvindi, Pietro Giorgio; Pasta, Salvatore; Raffa, Giuseppe Maria; Livesey, Steven
Abstract: We performed a pre-dissection computational fluid analysis of an ascending aortic aneurysm associated with unicuspid aortic valve. The analysis showed an abnormal helical flow pattern inside the aneurysm and an increased wall stress on the right postero-lateral wall of the ascending aorta. These values were largely higher than the theoretical cut-off for aortic wall dissection, their topographic distribution followed the intimal tear site as subsequently diagnosed by computed tomography scan and confirmed during the operation for dissection repair.